Non-fouling flow reactors for nanomaterial synthesis. Issue 5 (1st February 2023) - Besenhard, Maximilian O.; Pal, Sayan; Gkogkos, Georgios; Gavriilidis, Asterios
Abstract : This review provides a holistic description of flow reactor fouling for wet-chemical nanomaterial syntheses. Fouling origins and consequences are discussed together with the variety of flow reactors for its prevention. Abstract : The potential of flow chemistry for nanomaterial synthesis has been amply demonstrated in the last decade. Robust and reproducible synthetic protocols, scalability, high-throughput screening and novel process conditions are the main drivers to "go flow". Not always acknowledged, is how reactor fouling restricts the operation of flow reactors making it a bottleneck for nanomaterial flow synthesis. Even though remarkable achievements in process and reactor design have been made, providing solutions to minimise and prevent fouling, there is no single non-fouling flow reactor suitable for nanomaterial synthesis at all relevant synthetic protocols. There are, however, reactor designs and operations that can prevent fouling, depending on the nature of the synthesis, i.e., the particle formation mechanism and kinetics. Although the expression "fouling" is used generically, neither its causes, nor its circumvention can be generalised. Therefore, this review describes the diverse origins and consequences of flow reactor fouling for wet-chemical nanomaterial syntheses, and most importantly, showcases the variety of reactor designs and operations to mitigate or prevent fouling. The reactor characteristics are discussed with respect to the critical synthetic conditions aiming to guide the customisation of non-fouling flow reactors for a broad variety of continuous nanomaterial syntheses. For a successful flow synthesis, the flow reactor elements must be selected considering the possible fouling causes and consequences and how to mitigate (or at least monitor and detect) fouling, while providing the synthetic conditions required.